IFI44L as a Forward Regulator Enhancing Host Antituberculosis Responses - Haiqin Jiang; Lemuel Tsang; Hongsheng Wang; Changhong Liu (Journal of Immunology Research)
Interferon-induced protein 44-like (IFI44L) gene is a type I interferon-stimulated gene (ISG) that plays a critical role in antiviral activity and constitutes a promising diagnostic marker. However, its precise role and function in tuberculosis have not been unveiled. This study showed that IFI44L acts as an antimicrobial target and positive modulator in human macrophages. Knockdown of IFI44L led to increased Mycobacterium tuberculosis intracellular survival. Moreover, IFI44L was significantly upregulated, and it restricted the intracellular survival of M. tuberculosis H37Rv strains at 72 h after rifampicin treatment. Individuals with cutaneous tuberculosis (CTB) were found to have significantly higher IFI44L expression after 6 months of rifampicin therapy than after only 1 month. These results demonstrated that IFI44L induced positive regulation and clearance of M. tuberculosis from human macrophages. This antimicrobial activity of IFI44L makes it a possible target for therapeutic applications against M. tuberculosis.